2019
DOI: 10.1002/jmd2.12078
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of lysosomal diseases by screening of cases of idiopathic splenomegaly and/or thrombocytopenia with a next‐generation sequencing gene panel

Abstract: Lysosomal diseases (LD) are a group of about 70 rare hereditary disorders (combined incidence 1:5000) in which diverse lysosomal functions are impaired, impacting multiple organs and systems. The first clinical signs and symptoms are usually unspecific and shared by hundreds of other disorders. Diagnosis of LD traditionally relies on performing specific enzymatic assays, if available, upon clinical suspicion of the disorder. However, the combination of the insidious onset of LD and the lack of awareness on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In particular, our results indicate that the use of methods suitable for the detection of CNV due to deleted or recombinant alleles became mandatory when mutations in homozygosity were identified by CES. Moreover, this approach should be considered when using NGS for the study of conditions associated with mutations in different genes, including GBA , such as Parkinson’s disease [ 33 ], dementia with Lewy bodies [ 34 ], lysosomal diseases [ 35 ], and inherited platelets disorders [ 36 ]. Finally, other genes that are characterized by the presence of high homologous sequences or pseudogenes might benefit from the adoption of this integrated molecular strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our results indicate that the use of methods suitable for the detection of CNV due to deleted or recombinant alleles became mandatory when mutations in homozygosity were identified by CES. Moreover, this approach should be considered when using NGS for the study of conditions associated with mutations in different genes, including GBA , such as Parkinson’s disease [ 33 ], dementia with Lewy bodies [ 34 ], lysosomal diseases [ 35 ], and inherited platelets disorders [ 36 ]. Finally, other genes that are characterized by the presence of high homologous sequences or pseudogenes might benefit from the adoption of this integrated molecular strategy.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allowed for both lowering the costs and enhancing the diagnostic effectiveness. Recent studies reported NGS-based analyses in LD genetic diagnosis [ 8 , 9 , 10 , 11 ]. CNV detection was reported in only one study that included 28 LD genes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported NGS-based analyses in LD genetic diagnosis [ 8 , 9 , 10 , 11 ]. CNV detection was reported in only one study that included 28 LD genes [ 11 ]. Of note, the present work enabled the analysis of CNVs, not reachable by Sanger sequencing, for all the included 51 LD-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such NGS strategies allow the identification of single base pair variants and recombinant alleles (excluding the Recdelta55) with high specificity and sensitivity [167,169]. Conversely, analysis of the GBA1 gene as part of gene panels using well designed NGS strategies that consider the presence of the pseudogene, allows only the identification of point mutations, while fail to identify both large deletions and recombinant alleles due misalignment of reads with the homologous pseudogene [170][171][172][173][174].…”
Section: How Should Molecular Testing Be Performed?mentioning
confidence: 99%